2004
DOI: 10.1211/0022357022539
|View full text |Cite
|
Sign up to set email alerts
|

Is nose-to-brain transport of drugs in man a reality?

Abstract: The blood-brain barrier that segregates the brain interstitial fluid from the circulating blood provides an efficient barrier for the diffusion of most, especially polar, drugs from the blood to receptors in the central nervous system (CNS). Hence limitations are evident in the treatment of CNS diseases, such as Parkinson's and Alzheimer's diseases, especially exploiting neuropeptides and similar polar and large molecular weight drugs. In recent years interest has been expressed in the use of the nasal route f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
263
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(269 citation statements)
references
References 78 publications
(93 reference statements)
6
263
0
Order By: Relevance
“…The olfactory region is the only site where the central nervous system (CNS) is in contact with the external environment due to the presence of the olfactory receptor neurons, whose axons end in the olfactory bulb. Illum and coworkers (2000;2004) [1,2] determined the existence of a direct pathway connecting nose to brain and provided details of the possible routes of entry of substances introduced into the nose of different animals and humans. The authors postulated that, depending on the size, charge and hidro or lipophilicity of the molecule, different substances could be transported into the brain.…”
Section: Drug Instillationmentioning
confidence: 99%
“…The olfactory region is the only site where the central nervous system (CNS) is in contact with the external environment due to the presence of the olfactory receptor neurons, whose axons end in the olfactory bulb. Illum and coworkers (2000;2004) [1,2] determined the existence of a direct pathway connecting nose to brain and provided details of the possible routes of entry of substances introduced into the nose of different animals and humans. The authors postulated that, depending on the size, charge and hidro or lipophilicity of the molecule, different substances could be transported into the brain.…”
Section: Drug Instillationmentioning
confidence: 99%
“…The scintigrams (Figure 3) clearly demonstrate major radioactivity accumulation in brain following intranasal administration. The literature (Chow et al, 1999;Illum, 2004) reveals that the drug uptake into the brain from the nasal cavity mainly occurs via the olfactory pathway through which the drug travels from the nasal cavity to CSF and/or brain tissue. It concluded that the amount of drug in the brain tissue after nasal administration attributed to this pathway.…”
Section: Gamma Scintigraphymentioning
confidence: 99%
“…A drug administered into the nasal cavity and deposited on the olfactory mucosa should have a good chance to reach the cerebrospinal fluid (CSF), upon diffusion across the mucosa itself. Afterwards, the drug could diffuse into the interstitial fluid and reach the olfactory and/or trigeminal nerve pathways, or the vascular, lymphatic or CSF pathways, eventually penetrating the brain parenchyma (Thorne & Frey, 2001;Illum, 2004). In general, the dose to be administered nasally will be such that the same level of concentration of compound in the blood over 24 h obtained as for oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it had been demonstrated that nasal route, a noninvasive delivery system, could produce higher bioavailability than oral route due to the decrease hepatic metabolism, shorter distance to brain target and easy penetration through the brain (Wang et al, 2006;Illum, 2004). Based on the beneficial effects of quercetin and nasal delivery system, we hypothesized that quercetin liposomes could protect against neurodegeneration in AD.…”
Section: Introductionmentioning
confidence: 99%